Tuning the Regioselective Functionalization of Trifluoromethylated Dienes via Lanthanum‐Mediated Single C−F Bond Activation. Issue 12 (1st February 2021) - Kumar, Tarun; Yang, Yan; Sghaier, Sirine; Zaid, Yassir; Le Goff, Xavier F.; Rousset, Elodie; Massicot, Fabien; Harakat, Dominique; Martinez, Agathe; Taillefer, Marc; Maron, Laurent; Behr, Jean‐Bernard; et al.
Abstract: The development of new fluorine‐containing building blocks and their efficient synthetic access is currently a challenging research field. Herein, the highly regio‐ and stereoselective addition of a large range of aldehydes onto trifluoromethylated benzofulvenes was achieved using a simple La/I2 /DIBAL‐Cl system via a selective C−F bond activation process. This versatile methodology provided homodienyl alcohols bearing a terminal CF2 ‐alkene with potential further applications, as shown by the dehydration to the first benzofulvenes carrying a difluorovinyl group. In addition, for certain electron‐poor aldehydes, unprecedented ipso substitution of the CF3 group in a diene was observed, which, according to DFT studies, is related to the presence of the large, Lewis‐acidic lanthanum metal. Abstract : Making it linear : The right combination of lanthanide metal and Lewis acid affords the regio‐ and stereoselective functionalization of trifluoromethylated dienes with a wide range of aldehydes. Unprecedented ipso substitution is observed, and the regioselectivity is investigated by DFT calculations.